SPE Annual Technical Conference and Exhibition 1982
DOI: 10.2118/11101-ms
|View full text |Cite
|
Sign up to set email alerts
|

Non-Darcy Compressible Flow of Real Gases in Propped Fracture

Abstract: The development of a simple hyraulically fractured gas well model is presented. A one-dimensional fracture flow model is used to investigate the effects of non-Darcy flow of a real gas in a hydraulically induced, vertical, propped fracture.A sensitivity analysis was performed on the inertial resistance factor 8, to determine how any variation in the value of 8 would affect performance predictions based on non-Darcy flow.It was observed that non-Darcy flow effects in the fracture may be significant especially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well. On the average, about 10% of the total fracture pressure drop can be attributed to turbulence effects (Kakar et al, 2004).…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 99%
“…Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well. On the average, about 10% of the total fracture pressure drop can be attributed to turbulence effects (Kakar et al, 2004).…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 99%